2021
DOI: 10.1101/2021.05.15.444169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lipid-mTORC1 nutrient sensing pathway regulates animal development by peroxisome-derived hormones

Abstract: Animals have developed many signaling mechanisms that alter cellular and developmental programs in response to changes in nutrients and their derived metabolites, many of which remain to be understood. We recently uncovered that glucosylceramides, a core sphingolipid, act as a critical nutrient signal for overall amino-acid level to promote development by activating the intestinal mTORC1 pathway. However, how the intestinal GlcCer-mTORC1 activity regulates development throughout the whole body is unknown. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 78 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, blocking peroxisome function by mutation of prx-11/PEX11 , which important for peroxisome proliferation(Li et al, 2021; Thieringer et al, 2003), also inhibited the FEDUS (Fig. 4G,H), even though prx-11 was not essential for L1 development (Li et al, 2021; Thieringer et al, 2003; Wang et al, 2013). These data suggested that NHR-49/80 dependent peroxisome activation plays a critical role in FEDUS.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, blocking peroxisome function by mutation of prx-11/PEX11 , which important for peroxisome proliferation(Li et al, 2021; Thieringer et al, 2003), also inhibited the FEDUS (Fig. 4G,H), even though prx-11 was not essential for L1 development (Li et al, 2021; Thieringer et al, 2003; Wang et al, 2013). These data suggested that NHR-49/80 dependent peroxisome activation plays a critical role in FEDUS.…”
Section: Resultsmentioning
confidence: 97%
“…2B, C). We then measured the mTORC1 activity by the relative intestinal nucleolar size labeled by the FIB-1 antibody (because mammalian phosphorylated-S6K antibodies could not recognize its C. elegans ortholog RSKS-1) (Li et al, 2021; Ma et al, 2016; Sheaffer et al, 2008; Zhu et al, 2021a). Interestingly, we found the mTORC1 activity was further reduced, rather than increased under the palmitate supplementation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations